The Effectiveness of Student-Chosen Pairs for Cooperative Learning - Robin Morelock (Networks: An Online Journal for Teacher Research, 2005)
Cooperative learning is a well-established technique for improving student learning. A large number of studies have shown that cooperative learning improves learning, understanding and remembering. It also helps students feel better about themselves, the class and their classmates. (Johnson, Johnson and Holubec 1993; Slavin 1991). My own experience as a Junior High science teacher leads me to agree with studies indicating the value of cooperative learning. This study, however, deals not with the value of cooperative learning, but with establishing the best grouping for cooperative learning. Research on grouping has not shown clear-cut results. Heterogeneous and homogeneous groups both seem to have merit in particular situations (Slavin 1990; Kulik and Kulik 1982). The question addressed in this study is whether allowing students to choose their own partners for cooperative learning pairs can be effective for learning and attitudes of eighth grade science students.